TJNPR 2021
DOI: 10.26538/tjnpr/v5i5.15
|View full text |Cite
|
Sign up to set email alerts
|

Wild Chamomile (Matricaria recutita L) from the Taounate Province, Morocco: Extraction and Valorisation of the Antibacterial Activity of its Essential Oils

Abstract: This species is considered to be one of the most famous medicinal plants commonly consumed as herbal teas and teas. Moreover, some statistics show that every day more than a million glasses of camomile tea are drunk. 8 The properties of M. recutita are numerous; therapeutic, cosmetic, agri-food, etc. 9 From one hand, this plant is used for the treatment of various diseases, including those related to inflammatory conditions, 2 bacterial and gastrointestinal infections, 10 muscle spasms, 11 etc. On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Das et al [82] assessed antimicrobial activity by the formulation of a pickering nanoemulsion of MCEO and confirmed the great antibacterial action on P. aeruginosa PMC 103, S. aureus ATCC 29,213 and E. coli PMC 201 for an MIC 90 equal to 1.02 µg/mL, 1.06 µg/mL and 2.19 µg/mL, respectively. Moreover, the extraction and valorization of the antibacterial activity of wild chamomile from the Taounate province, Morocco, stated comparable relevant inhibitory diameters and MICs [83].…”
Section: Antimicrobial Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…Das et al [82] assessed antimicrobial activity by the formulation of a pickering nanoemulsion of MCEO and confirmed the great antibacterial action on P. aeruginosa PMC 103, S. aureus ATCC 29,213 and E. coli PMC 201 for an MIC 90 equal to 1.02 µg/mL, 1.06 µg/mL and 2.19 µg/mL, respectively. Moreover, the extraction and valorization of the antibacterial activity of wild chamomile from the Taounate province, Morocco, stated comparable relevant inhibitory diameters and MICs [83].…”
Section: Antimicrobial Activitymentioning
confidence: 96%
“…The comparison of literature data about the antimicrobial effect of MCEOs have illustrated considerable levels of divergence [83,86,89,90]. In reality, numerous molecules were described as major phytochemicals of MCEO, in particular, E-β-farnesene (34.61 ± 3.79%) in the United Kingdom [91], α-bisabolol oxide B (51.428%), chamazulene/azulene (17.688%), trans-β-farnesene (6.953%) in Ethiopia (Mekonnen et al [86], α-bisabolol (56.86%), transtrans-farnesol (15.64%), cis-β-farnesene (7.12%) in Portugal [88], chamazulene (31.48%), bisabolol and bisabolone oxide (15.71%) in Brazil [81], trans-β-pharnesene (43.5%), bisabolol oxide B (9.0%) and bisabolone oxide A (8.5%) in Serbia [84].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…However, the EO was able to reduce biofilm formation and alginate production, showing efficiency in controlling biofilm-producing bacteria. On the other hand, results of both diffusion and dilution techniques showed that Bacillus subtilis was the most sensitive bacteria to M. chamomilla EO from Morocco [87]. In addition, the EO showed the largest inhibition zone against B. cereus and the smallest MIC and MBC values against S. aureus [97].…”
Section: Antibacterial Activitymentioning
confidence: 97%
“…Generally, the chemical composition varied significantly depending on the origin of the plants. The EO from Moroccan M. chamomilla obtained by microwave-assisted hydrodistillation showed 24 chemical components representing 98.49% of the total EO, with chamazulene (26.11%) as the main component, followed by cis-β-farnesene (11.64%) and eucalyptol (8.19%) [87]. In another study from Egypt, Abbas et al [13] compared the chemical composition of EO obtained from fresh and dried flowers using different techniques (sunlight, shade, oven, solar dryer, and microwave).…”
Section: Phytochemical Interestmentioning
confidence: 99%
“…Aromatic and medicinal plants are the most essential means of treating a variety of antimicrobial illnesses. They contain a variety of antimicrobial chemicals and have no adverse effects [6][7][8]. Furthermore, herbal medicines remain an essential source of treatment for serious diseases, particularly in underdeveloped countries, and 60-80% of the world's population still uses traditional medicines to treat common ailments [9,10].…”
Section: Introductionmentioning
confidence: 99%